ENVIRONMENTAL SAFETY OF CONSTRUCTION AS A FACTOR OF GRAPHOANALYTICAL MODELING OF PRODUCT PARAMETERS - Slesarev, Sciences; Makarova, Anastasia (Revista Inclusiones, 2020)
The methodology concept of building parametric series of unified building products is presented. The purpose of the work is to create a method that would enable consideration of environmental safety requirements at the stage of design of the size range of the building products line. Method simplicity is based on the assumption of linear correlation of building products use parameters and required environmental parameters. Existing lifecycle assessment methods are intended for the analysis of one-off products rather than a set (line) of similar unified products. The problem is that the known product lifecycle assessment methods and line product configuration management methods yield mutually exclusive results. This work proposes the data presentation method that combines graphic construction of a parametric series of unified products and graphic construction of environmental requirements to products and their manufacturing and operation techniques. The work uses the known map imposition method as an environmental assessment method. Imposing a layer with graphic information about interrelated design and operational parameters of a product on a layer of information on acceptable exposure of these products manufacture and operation processes helps the product designer choose parameters of the unified product that meet environmental requirements from a host of options.